Modifications of hemoglobin and myoglobin by Maillard reaction products (MRPs) - Ioannou, Aristos; Varotsis, Constantinos (My University, 2017)
High performance liquid chromatography (HPLC) coupled with a Fraction Collector was employed to isolate Maillard reaction products (MRPs) formed in model systems comprising of asparagine and monosaccharides in the 60–180˚C range. The primary MRP which is detected at 60˚C is important for Acrylamide content and color/aroma development in foods and also in the field of food biotechnology for controlling the extent of the Maillard reaction with temperature. The discrete fractions of the reaction products were reacted with Hemoglobin (Hb) and Myoglobin (Mb) at physiological conditions and the reaction adducts were monitored by UV-vis and Attenuated Total Reflection-Fourier transform infrared (FTIR) spectrophotometry. The UV-vis kinetic profiles revealed the formation of a Soret transition characteristic of a low-spin six-coordinated species and the ATR-FTIR spectrum of the HbMRP and Mb-MRP fractions showed modifications in the protein Amide I and II vibrations. The UV-vis and the FTIR spectra of the Hb-MRPs indicate that the six-coordinated species is a hemichrome in which the distal E7 Histidine is coordinated to the heme Fe and blocks irreversibly the ligand binding site. Although the Mb-MRPs complex is a six-coordinated species, the 1608 cm-1 FTIR band characteristic of a hemichrome was not observed.
Keywords: Acrylamide; Amide; Asparagine; Hemoglobin; Monosaccharide; Myoglobin; Hemoglobin